One-week vaginal brachytherapy schedule as exclusive adjuvant post-operative treatment in intermediate- and high-intermediate-risk endometrial cancer patients - De Sanctis, Vitaliana; Musio, Daniela; Felice, Francesca; Marampon, Francesco; Valeriani, Maurizio; Bonome, Paolo; Anzellini, Dimitri; Facondo, Giuseppe; Vullo, Gianluca; Massaro, Maria; Di Staso, Mario; Bonfili, Pierluigi; et al. (Journal of contemporary brachytherapy, 2020)
The aim of the study was to report survival outcomes and toxicities incidence by using one-week vaginal brachytherapy (VBT) schedule in intermediate- and high-intermediate-risk endometrial cancer patients. One hundred and eight patients were treated with exclusive high-dose-rate (HDR) brachytherapy short schedule (7 Gy/fraction/every other day/1 week). Acute and late rectal, urinary, and vaginal toxicities were recorded according to radiation therapy oncology group (RTOG) scores and late effects normal tissue task force - subjective, objective, management, analytic (LENT-SOMA) scores, respectively. Overall survival (OS), cause specific survival (CSS), and disease-free survival (DFS) were evaluated. Median follow-up was 44 months (range, 6-117 months). The 5-year OS, CSS, and DFS rates were 92.7%, 96.4%, and 89.5%, respectively. Seven of 108 (6.5%) patients relapsed after a median time of 31 months (range, 5-56 months). Death occurred in 6 patients. Four patients died for intercurrent causes without an evidence of disease. Acute bladder toxicity G1-G2 was reported in 11 of 108 (10%) patients, vaginal toxicity G1-G2 in 6 of 108 (5.5%), and gastrointestinal toxicity was observed in 3 of 108 (3%) patients. Late bladder and gastrointestinal G1 toxicities were reported in 4 of 108 (4%) and 1 of 108 (1%) patients, respectively. Late vaginal toxicity (G1-G2) was recorded in 3 of 108 (3%) cases. No grade 3-4 bladder, vaginal, and gastrointestinal toxicities were noted. Exclusive short course adjuvant VBT is an effective treatment in patients with early-stage endometrial cancer and provides good outcomes in terms of disease local control and DFS, with low rates of toxicity profile.